10g+11=-19

Simple and best practice solution for 10g+11=-19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10g+11=-19 equation:


10g+11=-19

We simplify the equation to the form, which is simple to understand
10g+11=-19

We move all terms containing g to the left and all other terms to the right.
+10g=-19-11

We simplify left and right side of the equation.
+10g=-30

We divide both sides of the equation by 10 to get g.
g=-3

See similar equations:

| -57/8n=-121/4 | | 2c+17=53 | | 8/9x=72 | | 6n(n+5)=66 | | -3/x-2+1-x/x | | 1/5m=-1 | | 6k-3k=12 | | 5(x+4)+2=2 | | 2x^2+4x-2.5=0 | | 200=6t^2+4.5t+74 | | 5(x+2)+2x=24 | | f(x)=(5x^2)-3 | | 2j^2-2j+3j-3=0 | | 6v^4w^4+8uv^2w=0 | | 20m^3+25m^2=0 | | -1.3x-9.4=0.4x+8.6 | | 3c^2+10c+3=0 | | ln(13)=ln(x+6)-ln(7) | | n=6t^2-4.5t+74 | | 126=(7+x)(12+x) | | -5/x-1+3-2x/x | | 12c^2-7c^3=0 | | 1x-0.2x= | | 2(4x+8)= | | 320-8q=120 | | 6x+8=9-(8x-8) | | 24x^3y^2+36xy^3= | | p^2-p-12=0 | | 2x^2-1x-40=0 | | 5(4x+2)=39 | | 3/4(7x-8)=-6 | | -8=-16y |

Equations solver categories